The Essentialities of Cloud Accounting Information System on The Operational Efficiency of Firms In Nigeria - Sunny Biobele Beredugo (Journal of Accounting and Taxation, 2023)
Novel accounting technology such as cloud accounting information system has taken the Centre stage in its presumed capacity to provide relevance online accounting and auditing solutions that are accessible from anywhere through the cloud service providers. It is no doubt that keeping pace with this accounting technology has comes with apprehension from target audiences, that have created apathy in the deployment of cloud accounting by some companies in Nigerian, due to some speculative drawbacks such as high security breaches, high cost of IT services, risk of unauthorized access and viruses among others. It is in this light, that the study firstly examined the essentialities of cloud accounting information system on the operational efficiency of firms in Nigeria and secondly evaluated if there are significant differences in the perception of respondents in deployment of cloud accounting on corporate exigencies in Nigeria. The survey research design was adopted to collect data from 385 respondents in 32 companies cutting across four sectors in Nigeria. The Chi-square and Analysis of Variance were used for the test of hypotheses and it was discovered that cloud accounting significantly enhances the operational efficiency of firms in Nigeria, while there were no significant difference in the perception of respondents in deployment of cloud accounting leading to increase in the risk of unauthorized access, weak or no access control and high cost of IT services etc. In all, the benefits of the deployment of cloud accounting outweighs the exposures and it was recommended among others that organizations should endeavour to implement substantial security measures to protect IT infrastructure through effective internal control architecture